The Impact of Human Settlement on Decreasing of the Agricultural Land Sharazoor District as an example - Sarkawt Hamakhursheed Ahmed; Huda Sabah Najmadin; Narmin Abdullah Muhammad (Zanco Journal of Human Sciences, 2025)
Human settlements, defined as groups of buildings and houses inhabited in a specific area, vary in size, ranging from small villages to large cities. Agricultural land is a crucial resource, and its preservation is vital. This study investigates the impact of human settlement expansion on the decline of agricultural land in Sharazoor district.The primary concern of this study is the link between increasing human settlements and decreasing agricultural land within the study area. We aim to demonstrate the district's expansion between 2000 and 2023 using Geographic Information Systems (GIS) and Remote Sensing programs to generate maps and tables. The research plan will introduce the study area, analyze natural population growth, examine methods of urban settlement expansion, and conclude by presenting findings. Our analysis reveals that the residential area in the district comprised 0.9% of the total area in 2000. However, by 2023, this area had grown to 1036.7 hectares, representing a 3.0% share of the total area.Based on these findings, it is imperative for stakeholders to prioritize vertical (columnar) expansion strategies over horizontal expansion to minimize the impact on agricultural land